(untitled) (Bioscience Journal, 2022)
Objective: To evaluate the effect of ellagic acid on the inhibition of matrix metalloproteinase by analyzing the quality of the adhesive interface with bond strength measures in periods of 24 hours and six months of storage. Method: 40 healthy human third molars were prepared with class I cavities (5x4x3mm). The teeth were divided into four experimental groups: Group 1- without application of ellagic acid and storage time of 24 hours; Group 2- with ellagic acid/24 hours; G3- without ellagic acid/six months; Group 4- with ellagic acid/six months. Then, the cavities were restored with Single Bond Universal adhesive and Z350 composite resin, with and without the previous application of ellagic acid. Subsequently, hourglass-shaped specimens were obtained and subjected to the bond strength (BS) test (n = 10) in a universal testing machine. The bond test was performed after 24 hours and six months of storage. For the standard evaluation (n = 3) the samples were infiltrated with silver nitrate and placed in a developing solution for analysis in a Scanning Electron Microscope (SEM). The data obtained were analyzed with the Kruskal-Wallis non-parametric test, showing a statistically significant difference. Results: The highest bond strength values were found for the 24-hour groups followed by the groups with six months of storage. For nano-infiltration, groups G1 and G2 showed lower infiltration than groups G3 and G4. Conclusion: The previous application of ellagic acid did not affect the BS of the adhesive interface of the adhesive system analyzed, regardless of storage time.